2008
DOI: 10.1007/s00464-008-9988-7
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of immediate bleeding during endoscopic submucosal dissection in gastric lesions

Abstract: The results of this study demonstrated that age and lesion location were related to the ESD procedure outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
79
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(80 citation statements)
references
References 19 publications
1
79
0
Order By: Relevance
“…It might be by reason that PPI was not fast acting, compared with more rapid effects of H 2 RA in reaching the optimal gastric pH [12,19]. Some studies reported bleeding and ulcer healing were associated with lesion size and tumor location [20,21], but it was difficult to stratify patients by these factors in our meta-analysis. Although Hp infection is generally accepted as a causal factor in the pathogenesis of peptic ulcer, a few studies revealed Hp status did not affect ulcer healing after ESD [22,23].…”
Section: Discussionmentioning
confidence: 66%
“…It might be by reason that PPI was not fast acting, compared with more rapid effects of H 2 RA in reaching the optimal gastric pH [12,19]. Some studies reported bleeding and ulcer healing were associated with lesion size and tumor location [20,21], but it was difficult to stratify patients by these factors in our meta-analysis. Although Hp infection is generally accepted as a causal factor in the pathogenesis of peptic ulcer, a few studies revealed Hp status did not affect ulcer healing after ESD [22,23].…”
Section: Discussionmentioning
confidence: 66%
“…22,26,27 Gotoda 28 demonstrated that the tumors located in the upper or middle third of the stomach, and those with ulcer were prone to perforate after ESD. In the present study, multivariate analysis failed to reveal a significant risk factor associated with post-ESD bleeding.…”
Section: Discussionmentioning
confidence: 99%
“…Oda et al reported that only location (upper and middle third) and size (≄ 31 mm) were associated with immediate bleeding [8] . In one report, younger age and the location of the lesions (upper and middle third) were associated with a higher frequency of immediate bleeding [9] . Bleeding can be somewhat reduced in areas with abundant blood vessels by strengthening the coagulation energy when precutting or dissection, but this increases the risk of perforation.…”
Section: Hemorrhagementioning
confidence: 99%